Analisis Kapasitas dan Efisiensi Pembersihan Mesin Pembersih Biji-Bijian Sistem Blower untuk Produksi Pakan Burung Olahan - Rofarsyam Rofarsyam (Universitas Muhammadiyah Yogyakarta, 2010)
The optimum cleaning capacity and efficiency of sheed processing in bird food production have been investigated by employing dimensional analysis. The types of grains, grain weight, blowing speed, hight and width of grain-fall were varied in order to obtaine the capacity, processing time and the cleaning degree data of the machine under investigation. The data were then analyzed to determine the product capacity-processing parameter, and efficiency-processing parameter relationships. It was con cluded that two mathematical model of product capacity-processing parameter relationship and efficiency-processing parameter relationship were governed from this study. These mathemetical models can be further used as a reference for determining the dimensions in manufacturing and operation blower system cleaning machine, in order to achieve its maximum cleaning capacity and efficiency.